2007
DOI: 10.1007/s12026-007-8005-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulation of fetal and anti-paternal immune responses

Abstract: Immunological tolerance to the fetus is essential for fetal survival during pregnancy. The semi-allogeneic fetus expresses genes foreign to the mother that can be recognized by maternal T cells. Under times of stress or infection, deleterious immune responses can result in fetal destruction and/or maternal death. Exposure to non-maternal antigens begins as early as insemination and some of the mechanisms required to prevent maternal priming against these antigens are in place before sexual encounter. Continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 88 publications
0
19
0
Order By: Relevance
“…While some essential 1,25(OH) 2 D 3 functions in female fertility relate to reproductive tissue development [262,263], other functions probably relate to immune tolerance induction and are highly relevant to the protective effects of pregnancy in women with MS. The semi-allogeneic, fetal trophoblast cells must invade the uterine decidua to establish the fetal blood supply, but the uterine decidua harbors T lymphocytes capable of recognizing and attacking the fetal tissue bearing paternal antigens [264]. Incompletely understood mechanisms exist at the border between mother and fetus to promote maternal immune tolerance of the fetus without unduly compromising immune responses to infectious agents.…”
Section: Multiple Sclerosis Pregnancy and Immune Tolerancementioning
confidence: 99%
“…While some essential 1,25(OH) 2 D 3 functions in female fertility relate to reproductive tissue development [262,263], other functions probably relate to immune tolerance induction and are highly relevant to the protective effects of pregnancy in women with MS. The semi-allogeneic, fetal trophoblast cells must invade the uterine decidua to establish the fetal blood supply, but the uterine decidua harbors T lymphocytes capable of recognizing and attacking the fetal tissue bearing paternal antigens [264]. Incompletely understood mechanisms exist at the border between mother and fetus to promote maternal immune tolerance of the fetus without unduly compromising immune responses to infectious agents.…”
Section: Multiple Sclerosis Pregnancy and Immune Tolerancementioning
confidence: 99%
“…þ T lymphocytes (both ab and gd T cells, with a greater proportion of gd cells), and a subset of lymphocytes, natural killer T (NKT) cells [Dang et al 2000;Hunt 2006;Seavey and Mosmann 2008]. Neutrophils and monocytes circulate throughout the maternal placental vasculature and have been shown to infiltrate areas of infection, damage, or resorption [Girardi 2008;Girardi et al 2003;Rogerson et al 2003].…”
Section: Immunology Of Pregnancymentioning
confidence: 99%
“…Proper establishment, progress and success of mammalian pregnancy rely on the capability of the maternal immune system to undergo a series of adaptations tending to tolerate the presence of the semi-allogeneic fetus (Robertson and Moldenhauer, 2014;Seavey and Mosmann, 2008). Among others well described immune-mechanisms; our laboratory has demonstrated that pregnancy induces strong modifications in B cell development (Muzzio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%